Marginal Micro-leakage of Self-etch and All-in One Adhesives to Primary Teeth, with Mechanical or Chemo-Mechanical Caries Removal - Nouzari A; Zohrei A; Ferooz M; Mohammadi N (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Chemo-mechanical caries removal is an effective alternative to the traditional rotary drilling method. One of the factors that can influence micro-leakage is the method of caries removal. Objectives: To compare the micro-leakage of resin composite in primary dentition using self-etch and all-in one adhesives following conventional and chemo-mechanical caries removal. Materials and Methods: Sixty extracted human primary anterior teeth with class III carious lesions were collected. The selected teeth were divided randomly into two groups each consisting of 30 teeth. In group1 carious lesions were removed using Carisolv multi mix gel. In group 2, caries was removed using round steel burs in a slow-speed hand piece. Then, the specimens in each group were randomly divided into two subgroups (A and B) of 15 and treated by either Clearfil SE Bond (CSEB) or Scotch bond. All prepared cavities were filled with a resin composite (Estellite). All the specimens were stored in distilled water at 37ºC for 24 hours and then thermocycled in 5ºC and 55ºC water with a dwell time of 20 seconds for 1500 cycles. The specimens were immersed in 1% methylene blue solution for 24 hours, removed, washed and sectioned mesiodistally. The sectioned splits were examined under a stereomicroscope to determine the micro-leakage scores. The data were analyzed using Kruskal-Wallis Test in SPSS version 21. Results: There were no significant differences between micro-leakage scores among the four groups (p = 0.127). Score 0 of micro-leakage was detected for 60% of the specimens in group 1-A (Carisolv + CSEB), 73% of the group 2-A (hand piece + CSEB), 80% of the group 1-B (Carisolv + Scotch bond), and 93% of the group 2-B in which caries was removed using hand piece and bonded with Scotch bond . Conclusions: Although caries removal using hand piece bur along with using Scotch bond adhesive performed less micro-leakage, it would seems that the use of Carisolv doesn't adversely affect the micro-leakage of composite restorations while using self-etch or all-in one adhesives.